Factors associated with mortality in patients hospitalized for COVID-19 in Peru. A systematic review - Villanueva Díaz, María Ysabel (2024)
Introduction: The COVID-19 pandemic has spread globally, with Peru being one of the countries with the highest mortality in the world. Therefore, the aim of this study was to evaluate the factors associated with mortality in patients hospitalized for COVID-19 in Peru.Material y methodos: A systematic review of the literature was carried out using the databases PubMed, Scopus, Web of Science, Embase, the Virtual Health Library, Scielo, and Google Scholar until September 13, 2023. The main search terms used were "COVID-19", "mortality," and "Peru". Results: A total of 1876 articles were retrieved using the search strategy. After removing duplicates (n = 528) and screening by title, abstract, and full text, 27 observational studies were included that met the inclusion criteria, with a total sample of 10154 hospitalized patients with COVID-19. Of the total participants, 65.59% were male, with a mean age over 55 years. The studies were conducted in nine regions of Peru. The mortality rate of adult patients ranged from 6.8% to 71.83%. The most prevalent associated factors were advanced age, male sex, presenting comorbidities such as hypertension, diabetes, and obesity, laboratory markers such as lymphocytopenia, lactate dehydrogenase, C-reactive protein, D-dimer, total bilirubin, oxygen saturation below 80%, use of hydroxychloroquine, ivermectin, or azithromycin, and corticosteroids. Conclusions: Age, male sex, cardiovascular disease, lactate dehydrogenase, C-reactive protein, D-dimer, oxygen saturation below 80%, and ivermectin were the most prevalent factors associated with mortality in Peruvian patients hospitalized for COVID-19.